Transformasi Sosial Ekonomi Penduduk Lokal Akibat Adanya Pembangunan Di Kawasan Solo Baru Kabupaten Sukoharjo - Lintang Rahmayana; Wiwandari Handayani (Jurusan Perencanaan Wilayah dan Kota, 2016)
Solo Baru Region is located in Grogol, Sukoharjo District. Formerly, Solobaru was a rural region, but with the building that was caused by the development of urban, makes the Solo Baru Region being urban built up area. Where there is the largest mall in Sukoharjo, the elite housing, apartments and hotels etc. The changes impact the socio- economic structural in its local communities. Based on these matters raise the question of how the socio-economic transformation of the local residents due to the construction in the area of Solo Baru? The research method in this study using quantitative methods with descriptive format in whict the data is obtained from the questionnaire and fiel survey. Weighting for the variables using analytic pairwise method technique. Based on the analysis can be seen there has been a change in the socio-economic of its local communities in Solo Baru Region due to the development in the area. The greatest changes are on the economic aspect, while social changes are likely not to be too large because of changes in this aspect is slow. Changes in social aspects can be evidenced by 43% of respondents feel the changing skills, 18.8% of respondents feel the decline in customs, and in terms of accessibilities there are approximately 48.50% of respondents reporting an increase in the number of trips. As for changes in the economic aspects can be evidenced by 95% of respondents experienced an increase in revenue. In addition to a change in the livelihood of 63.40% of respondents. The majority of respondents who changed in livelihood are become the sellers.